A Method for Modeling Variation of In Situ Stress Related to Lithology - J. K. Whyatt (The National Institute for Occupational Safety and Health (NIOSH))
Assuring ground control safety in many mining and tunneling projects depends, at least in part, on an understanding of in situ stress conditions that will be encountered. Yet it is rarely practical to conduct more than a very limited number of stress measurements. Stresses along the route of a proposed excavation are typically interpolated from available measurements, often assuming a linear variation of stress with depth (or elevation). However, projects where multiple stress measurements are conducted often report more complex variations of in situ stress, usually in apparent relationship to geologic structures. These structures often include lithologies of contrasting elastic properties. A method is proposed for estimating stresses in these cases by first back-calculating regional loads from available stress measurements and then modeling the distribution of stress throughout the rock mass. The method has been successfully applied to a set of in situ stress measurements from the Coeur d’Alene Mining District of northern Idaho, USA. Results provided new insights into district stress conditions and the distribution of rockburst hazards along mine drifts and between various mines. This success should transfer readily to suitable deep tunneling projects.